Structured patient interview to assess clinical outcomes in complicated urinary tract infections in the APEKS-cUTI study: pilot investigation - Simon Portsmouth (SAGE Publishing, 2021)
Background: The APEKS-cUTI study demonstrated the non-inferiority of cefiderocol to imipenem−cilastatin in the primary endpoint of the composite of clinical and microbiological outcome in patients with complicated urinary tract infections (cUTIs). We piloted a structured patient interview (SPI) to evaluate clinical outcomes based on patient-reported symptoms while conducting this pivotal randomized, double-blind, phase-2 study. The objectives were to assess the value of the SPI, using its performance relative to physician assessment, and also to strengthen the value of patient-reported measures in conducting clinical trials for cUTI treatment. Methods: In addition to the protocol-defined clinical and microbiological outcomes, patients randomized in the APEKS-cUTI study were interviewed by the investigator or qualified study personnel at screening/baseline, early assessment (EA), end of treatment (EOT), test of cure (TOC), and follow-up (FUP). The 14-element questionnaire graded cUTI symptoms as absent or present, and if present, as mild, moderate, or severe. Changes in post-baseline symptoms based on patients’ responses were rated by the interviewer. The overall clinical outcome was evaluated based on the responses provided by patients at each time point. Results: Among the 371 patients in the modified intention-to-treat population, the rate of SPI completion in each treatment arm exceeded 90% at each time point. SPI-assessed clinical cure rates were 89.7% in the cefiderocol arm and 84.9% in the imipenem–cilastatin arm. There was substantial agreement between SPI evaluation and investigator global assessment of clinical outcome at TOC and FUP, with lower agreement at EA and EOT. Conclusion: This analysis suggests that patient-reported symptoms can be effectively captured in hospitalized patients with cUTI in a clinical trial setting. Development of a validated patient-reported outcome for use in such a setting is warranted. Registration: NCT02321800 (registered on 22 December 2014).